Convergence of a semi-Markov process and an accompanying - Malik, V. F.; Samoilenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We propose an approach to the proof of the weak convergence of a semi-Markov process to a Markov process under certain conditions imposed on local characteristics of the semi-Markov process.